2000
DOI: 10.1007/pl00008886
|View full text |Cite
|
Sign up to set email alerts
|

Morphological defenses induced in situ by the invertebrate predator Chaoborus: comparison of responses between Daphnia pulex and D. rosea

Abstract: The presence of plankton predators may induce altered morphology in their potential prey. To date, the mechanism of induction and adaptive value of such defensive responses have been examined in the laboratory. This study investigated the morphological defense structures induced by the invertebrate predator Chaoborus in two coexisting Daphnia species, D. pulex and D. rosea, in the field. In Piscivore Lake (Gräfenhain, Germany), continuous and intense biomanipulation had led to near elimination of planktivorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 71 publications
(80 reference statements)
2
30
0
1
Order By: Relevance
“…The presence of Chaoborus strongly reduces the chances of individuals reaching maturity (Sell 2000(Sell , 2006. A slight increase of the total population density should have been observed in August due to the absence of a high predation rate.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Chaoborus strongly reduces the chances of individuals reaching maturity (Sell 2000(Sell , 2006. A slight increase of the total population density should have been observed in August due to the absence of a high predation rate.…”
Section: Discussionmentioning
confidence: 99%
“…They may take the form of novel physical structures, as in daphnids (Sell 2000;Tollrian 1993), or via changes in existing morphology, such as tail depth and colour in anuran larvae (Relyea and Werner 2000;Van Buskirk and Relyea 1998). Such changes in morphology are predicted to come with costs, and this cost-benefit scenario generates less predictable life history outcomes.…”
Section: Expectationsmentioning
confidence: 99%
“…Induction of morphological defences in Daphnia populations by either fish or invertebrate predators is well studied under experimental conditions (Spaak & Boersma, 1997;Kolar & Walh, 1998;Sell, 2000) but more rarely in field studies (Havel & Dodson 1985;Lindholm, 2002). Several experimental studies showed that Daphnia respond to fish kairomones by increasing tail spine length (Tollrian, 1994;Spaak & Boersma, 1997), whereas elongation of the helmet or formation of a neck tooth are common responses of Daphnia to invertebrate predators (mainly Chaoborus) (Tollrian, 1993;Brancelj et al, 1996;Sell, 2000).…”
Section: Introductionmentioning
confidence: 99%